Renal function, N-terminal Pro-B-type natriuretic peptide, propeptide big-endothelin and patients with heart failure and preserved ejection fraction - Gergei, Ingrid; Krämer, Bernhard; März, Winfried (Peptides, 2019)
Renal dysfunction may limit the clinical application of NT-proBNP in the diagnosis of heart failure. In general practice, where echocardiography is not readily available, a biomarker for the diagnosis of a heart failure with preserved ejection fraction (HFpEF) would be useful. Since cardiac diseases frequently coincide with renal disease, there is a high need of valid risk stratification methods in patients affected with both. We therefore examined NT-proBNP and another biomarker, Big-Endothelin-1, as a marker of HFpEF in patients with CKD. NT-proBNP and Big-ET-1 were determined in 439 patients with HFpEF in the Ludwigshafen Risk and Cardiovascular Health (LURIC) study. NT-proBNP plasma level has shown an exponential increase with declining GFR, while Big-ET-1 plasma level increased only in a moderate and linear fashion. In patients without CKD, a NT-proBNP cut-off point at 250pg/mL was suitable for the discrimination between HFpEF and patients without HF. When the GFR was less than 60mL/min/1.73m2, the NT-proBNP cut-off point should be raised to 750pg/mL. At a cutoff point at 0.85 fmol/L, Big-ET-1 allowed to distinguish patients with HFpEF from persons without HF, independently of GFR. In general, NT-proBNP is a good indicator of suspected heart failure. While for NT-proBNP different cut-off points have to be considered in the diagnosis of HFpEF, a single cut-off point of Big-ET-1 was appropriate in the diagnosis of HFpEF, regardless of the presence or absence of CKD. An additional measurement of Big-ET-1 improves the diagnosis of HFpEF in patients with chronic kidney disease.
Available online 21 April 2018
Gesehen am 29.03.2019